Cultural Branding of Serang Batik Ambassadors Amidst Modernization Challenges - Dinda Raychana; Alis Triena Permanasari; Giri Mustika Roekmana; Wiwin Purwinarti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the role of the Serang City Batik Ambassadors in building the cultural brand of traditional textiles amid the growing tide of modernization. The phenomena of globalization and the development of information technology have brought significant changes to local culture, including traditional batik as a symbol of regional cultural identity. In this context, the Serang City Batik Ambassadors serve as cultural agents who play a role in strengthening the image of batik, introducing it to the public, and preserving its cultural values, particularly among the younger generation. This study employs a qualitative approach using the case study method. Data collection techniques included interviews, observations, and documentation of the activities of the Serang City Batik Ambassadors. The results indicate that the Serang City Batik Ambassadors play a strategic role in building cultural branding through promotional activities, educational initiatives, and participation in various cultural and social events. Furthermore, the Batik Ambassadors contribute to raising public awareness of the importance of preserving batik as a local cultural heritage amid the rapid pace of modernization. Thus, the Serang City Batik Ambassadors serve not only as cultural symbols but also as key actors in strengthening a regional cultural identity that is adaptable to the changing times.